Percepção do usuário sobre o acolhimento em um serviço de assistência especializada à saúde de pessoas vivendo com HIV em uma metrópole amazônica - PINTO, Gabriel Jardim da Motta Corrêa (2023)
HIV can affect all people regardless of age group or various other sociodemographic aspects, in addition to causing great dysfunction in the infected individual's organism, configuring a health condition loaded with a stigmatizing history. The National Humanization Policy (PNH) was created in 2003 to implement the principles of the SUS specifically focused on everyday care and management practices. Among its guidelines, the PNH has welcoming as one of its main consulting axes, which proposes attitudes of inclusion, commitment and solidarity with the demands of users. In this sense, the assistance offered must include the reception on a daily basis in their daily activities for an attention focused on the control of HIV/AIDS in order to reduce abandonment and prejudice against people with the virus. Thus, the study aims to evaluate the reception provided by the multiprofessional team, based on the user's perception. This is a descriptive and exploratory study, with a qualitative and quantitative approach, carried out at the Specialized Care Service (SAE), located in Belém (PA), a reference in the metropolitan region. Data were obtained from the application of the questionnaire to patients in the months of September and October 2022, with questions focused on sociodemographic aspects, treatment and the user's perception of reception. Eighty-nine questionnaires were collected, with a predominance of males (82%), aged between 20 and 29 years (31.4%), homosexuals (51.9%), single (68.5%), with high school (44.3%), with travel time to the SAE less than 1 hour (47.1%), working formally or informally (66.3%), with income between 1 and 3 minimum wages (52.4%) and time of diagnosis between 1 and 5 years (38.2%). As for treatment, most claim to have started less than 1 year ago (35.9%) and denied changes in ART (68.5%). Those who abandoned ART represent a minority (16.9%). Of the reasons for dropping out, the main one was “Disappointment/Demotivation” (60%). Regarding the reception, most participants believe that they were welcomed (87.6%) and that the reception was important to continue the treatment (93.2%). Multiprofessional care was generally assessed as satisfactory, with a satisfaction rate between 76.1% and 49.4%. Most participants say that there was no value judgment between their appointments (78.2%), as well as their freedom was respected (90.9%) along with the freedom and autonomy to start treatment (95.5%). From the analysis, the potential of offering care to this clientele is evidenced as largely consistent with the principles and guidelines of the PNH. There is also a need for legal reinforcement and an active search for the best solutions for the effectiveness of actions in the field of multidisciplinary care demanded by some patients.